Program Mengajar Sekolah Tingkat Dasar di SD Negeri 5 Duda Timur Karangasem Bali - Ida Ayu Anggreni Suryaningsih; I Nengah Sandi Artha Putra; Pande Putu Wulandari; Apriana Zebua; Ade Pebrianti Madia Sari (Pubfine Media Group, 2024)
Teaching activities are carried out at SD Negeri 5 Duda Timur Karangasem Regency. Teaching activities are one of the activities that must be carried out by Triatma Mulya University students. Teaching activities carried out include the preparation stage, teaching practice, and analysis of results. Some of the teaching preparations carried out include consultation activities with supervising teachers regarding student conditions and potential, supporting facilities in Teaching and Learning Activities (KBM), and also inhibiting factors that are often encountered when Teaching and Learning Activities (KBM) take place and direct observation. In this case, before carrying out teaching activities, students made observations of learning activities at SD N 5 Duda Timur. The teaching practice was carried out from January 14, 2024, to January 19, 2024. After carrying out the teaching practice, the results were that the students of SDN 5 Duda Timur, on average, had good seriousness in learning, especially in learning basic English, recognizing colors, and it was hoped that all the learning that had been carried out can be widely useful for students at SDN 5 Duda Timur.